SOCIAL PSYCHOLOGICAL CONDITIONS FOR THE DEVELOPMENT OF PSYCHOLOGICAL STABILITY OF MILITARY UNIVERSITY CADETS - Abdurakhmanova R. I. (Scholars Digest Publishing, 2023)
The article reveals the term, psychological stability and the conditions for its development in conditions of strict discipline. Psychological resilience covers a wide range of psychological and emotional characteristics that enable military personnel to function effectively in their service environment and overcome the challenges they face. Research shows that military personnel with high psychological resilience are more likely to successfully complete assigned tasks, overcome challenges, and strive to achieve their goals.
Keywords: psychological stability (instability), self-control, emotional stability, adaptation, difficulties, endurance, professional training, poise, regulation.